2019
DOI: 10.1016/j.aninu.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-glucan supplementation improves growth performance, carcass traits and meat quality of finishing pigs

Abstract: This experiment was conducted to investigate growth performance, carcass traits and meat quality of finishing pigs with dietary β-glucan supplementation. A total of 96 healthy pigs (Duroc × Landrace × Yorkshire; initial average BW = 25 kg) were randomly allocated into 4 dietary treatments with 6 replicates per treatment and 4 pigs per replicate. The control group was fed a basal diet, and the experimental diets were supplemented with 50, 100 and 200 mg/kg Agrobacterium sp. ZX09 β-glucan, respectively. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 27 publications
4
39
1
1
Order By: Relevance
“…In recent years, carcass traits are crucial indices reflecting livestock production in animal husbandry [27][28][29]. Francisco et al [30] showed that the live BW and diet composition were two main factors associated with carcass traits, and these observations were also found in our study.…”
Section: Carcass Traitssupporting
confidence: 86%
See 1 more Smart Citation
“…In recent years, carcass traits are crucial indices reflecting livestock production in animal husbandry [27][28][29]. Francisco et al [30] showed that the live BW and diet composition were two main factors associated with carcass traits, and these observations were also found in our study.…”
Section: Carcass Traitssupporting
confidence: 86%
“…Furthermore, Cortese et al [31] reported that the carcass yield of Charolais bulls was not affected by increased dietary protein levels. Luo et al [28] also showed that there were no differences in backfat thickness and carcass yield in fattening pigs fed with different levels of β-glucan supplementation. The above results were consistent with the results of this study.…”
Section: Carcass Traitsmentioning
confidence: 98%
“…In broiler, Soliman et al (2014) found that the addition of different levels of mannan and β-Glucan as a prebiotic to broilers diets contaminated with aflatoxin might be reduced the effects of aflatoxin toxicity on body weight. In pigsBG has a considerable effect on fishing pig growth, according to Luo et al (2019). At the early stage and throughout the fattening period, the supplementation of 100 mg/kg BG considerably boosted the daily gain and improved the feed to gain relative amount.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier researches, BG supplementation in the feed has been shown to improve poultry growth and immunity (Soliman et al, 2014;Tian et al, 2016), pigs (Wang et al, 2008;Luo et al, 2019), rats (Belobrajdic et al, 2015), cattle calves (Tao et al 2015), fish (Cao et al, 2019;Dawood et al, 2020), rabbits (García-Ruiz et al, 2008;Abo Ghanima et al, 2020). Contrary, Supplementing rabbit diets with yeast-glucans has no effect on growth or digestibility (Guenaoui, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The mushrooms' β-glucan contents ranged from 0.21% to 0.53% (dry weight basis) [35]. As Luo et al (2019) [36] indicated, β-glucan was a sort of functional polysaccharide that widely existed in the cell wall of fungi and possessed many biological activities. Previous studies showed that pigs fed β-glucan diets might enhance growth performance, which was probably due to the intestinal improvement, as β-glucan could modulate intestinal structure and morphology [30,37,38].…”
Section: Discussionmentioning
confidence: 99%